2012
DOI: 10.1136/bjsports-2012-091718
|View full text |Cite
|
Sign up to set email alerts
|

Do changes to the local street environment alter behaviour and quality of life of older adults? The ‘DIY Streets’ intervention

Abstract: BackgroundThe burden of ill-health due to inactivity has recently been highlighted. Better studies on environments that support physical activity are called for, including longitudinal studies of environmental interventions. A programme of residential street improvements in the UK (Sustrans ‘DIY Streets’) allowed a rare opportunity for a prospective, longitudinal study of the effect of such changes on older adults’ activities, health and quality of life.MethodsPre–post, cross-sectional surveys were carried out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
104
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(107 citation statements)
references
References 33 publications
0
104
0
3
Order By: Relevance
“…Because the five positive associations were observed only in two studies (25,39) within the same study population, general conclusions cannot be drawn about perceived accessibility. Overall, ten studies did not find significant associations between changes in the built environment and changes in physical activity (56)(57)(58)(59)(60)(61)(62)(63)(64)(65).…”
Section: Summary Of Evidencementioning
confidence: 92%
“…Because the five positive associations were observed only in two studies (25,39) within the same study population, general conclusions cannot be drawn about perceived accessibility. Overall, ten studies did not find significant associations between changes in the built environment and changes in physical activity (56)(57)(58)(59)(60)(61)(62)(63)(64)(65).…”
Section: Summary Of Evidencementioning
confidence: 92%
“…Yet, evidence would suggest the majority of older adults are not sufficiently active, and consequently fail to meet recommended levels of PA (Ward-Thompson et al 2014). In the United Kingdom (UK), less than 25% of adults meet the recommended daily levels of physical activity, and thus are considered to be at a greater risk of induced medical conditions including; cardiovascular disease, type 2 diabetes mellitus, obesity, and some associated cancers (Fife-Schaw et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Four (out of four) studies showed significant impacts on health and environmental factors for interventions involving greening of urban streets. Ward Thompson et al (2014) found evidence to support the provision of so-called 'DIY streets' in urban areas in the UK. Streets were made safer and more attractive (e.g.…”
Section: Greening Interventionsmentioning
confidence: 99%